ANALISIS DAMPAK KEBIJAKAN PENERIMAAN PESERTA DIDIK SEKOLAH MENENGAH PERTAMA 3 SEMARANG ( KAJIAN PERATURAN KEPALA DINAS PENDIDIKAN KOTA SEMARANG 420/3271 TENTANG PETUNJUK TEKNIS PENERIMAAN PESERTA DIDIK REGULER DI KOTA SEMARANG 2010/2011 ) - Pandu Pratomo; Sri Suwitri; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The problem admission process in SMP 3 Semarang was always about the achievement scores of the prospective students that applied to SMP 3 Semarang. This problem is getting worst and more complex by years, so SMP 3 Semarang is trying to prevent it by making a policy that oblige all prospective students that want to apply to SMP 3 Semarang by using the achievement scores to undergo the achievement scores test done by the school admission committee and oblige to sign a stamped statement that acknowledge the truth of their achievement scores as well. This research aims to identify and analyze the policy impact of school admission policy made by SMP 3 Semarang and to find out all the supporting and impeding aspects during the policy implementation/practice. The research uses descriptive qualitative. In conclusion The research showed that this policy that have been made by SMP 3 Semarang have both internal and external effects, in the form of positive responds giving by public and the Education Board itself already fully support as well the policy that oblige all prospective students that want to apply by using the achievement scores must undergo the achievement scores test done by the school admission committee and oblige to sign a stamped statement that acknowledge the truth of their achievement scores. This policy is having effect on SMP 3 Semarang as well in the form of the descent rate of fraud in the school admission process in SMP 3 Semarang, so the school quality is maintained